2017
DOI: 10.2495/bim170131
|View full text |Cite
|
Sign up to set email alerts
|

Bim in French Smes: From Innovation to Necessity

Abstract: Building Information Modeling (BIM) arrives in great strength in France and in Europe. This process has been mainly recognized for its capacity to energize the building market by sustainable means and the digitization of the current work system. For the SMEs (a business needs to have fewer than 249 employees to be considered an SME), this vast development site proves to be a difficult shift to implement but one that is not to missed in order to gain competitiveness and be able to compete with markets that rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…(Bosch-Sijtsema et al, 2017) assert that the results from their study on SMEs indicated that more than half of medium-sized contractors in the sample used BIM in some projects and the main obstacles for BIM implementation is related to the lack of normative pressure. (Tranchant et al, 2017) carried out an immersive 3D projection for the simulation of the Ajaccio hospital in France. According to (Tranchant et al 2017), the heart of the economy of France is that of SMEs, which represents 96% of companies.…”
Section: Information Requirements For Construction Companies In Renov...mentioning
confidence: 99%
“…(Bosch-Sijtsema et al, 2017) assert that the results from their study on SMEs indicated that more than half of medium-sized contractors in the sample used BIM in some projects and the main obstacles for BIM implementation is related to the lack of normative pressure. (Tranchant et al, 2017) carried out an immersive 3D projection for the simulation of the Ajaccio hospital in France. According to (Tranchant et al 2017), the heart of the economy of France is that of SMEs, which represents 96% of companies.…”
Section: Information Requirements For Construction Companies In Renov...mentioning
confidence: 99%
“…This configuration is not related to a specific country, but it is common for the sector. For example, in Italy around 96% of the construction companies have less than nine employees (ANCE 2017), in the UK 93% have less than 13 employees (DTI UK 2006), and in France (all sectors combined) 98.8% of companies are SMEs (Tranchant et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The objectives are then, to provide concrete assistance to companies willing to engage in BIM maturity levels by using all the information collected [3], [4]. This study is the opportunity to make links between different maturity models, from critical success factors to practical actions to implement in a company wishing to move toward the maturity levels of BIM [5], [6] BIM abroad and in France.…”
Section: Introductionmentioning
confidence: 99%